Redetermination of despujolsite, Ca(3)Mn(4+)(SO(4))(2)(OH)(6)·3H(2)O - Barkley, Madison C. (International Union of Crystallography, 2011)
The crystal structure of despujolsite [tricalcium manganese bis(sulfate) hexahydroxide trihydrate], the Ca/Mn member of the fleischerite group, ideally Ca(3)Mn(4+)(SO(4))(2)(OH)(6)·3H(2)O, was previously determined based on X-ray diffraction intensity data from photographs, without H-atom positions located [Gaudefroy et al. (1968 ▶). Bull. Soc. Fr. Minéral. Crystallogr. 91, 43–50]. The current study redetermines the structure of despujolsite from a natural specimen, with all H atoms located and with higher precision. The structure of despujolsite is characterized by layers of CaO(8) polyhedra (m.. symmetry) interconnected by Mn(OH)(6) octahedra (32. symmetry) and SO(4) tetrahedra (3.. symmetry) along [001]. The average Ca—O, Mn—O and S—O bond lengths are 2.489, 1.915, and 1.472 Å, respectively. There are two distinct hydrogen bonds that stabilize the structural set-up. This work represents the first description of hydrogen bonds in the fleischerite group of minerals.